2015
DOI: 10.1016/j.wre.2014.11.005
|View full text |Cite
|
Sign up to set email alerts
|

Integrating water resource management and land-use planning at the rural–urban interface: Insights from a political economy approach

Abstract: a b s t r a c tInstitutional obstacles to integrated water management at the river basin scale have been discussed in detail in the water governance literature, but there has been less attention to the development of analytical framework for understanding local government cooperation. In this study, a median voter model was developed to describe the political processes by which municipalities lend their support to land-use control in river basin management planning. Relative income, population growth, and land… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 47 publications
0
2
0
Order By: Relevance
“…Research has suggested different types of environmental zoning [5,12,15,16,24,27]. Designing EZ must be done according to the economic, social, environmental, political, and institutional needs of the inhabitants in the watershed.…”
Section: Environmental Zoning (Ez)mentioning
confidence: 99%
See 2 more Smart Citations
“…Research has suggested different types of environmental zoning [5,12,15,16,24,27]. Designing EZ must be done according to the economic, social, environmental, political, and institutional needs of the inhabitants in the watershed.…”
Section: Environmental Zoning (Ez)mentioning
confidence: 99%
“…Watershed management addresses anthropic problems [7], current land use [12], land use conflicts [13], excessive use of ecological resources [9], biological resources [14], water resources [15]. To solve these problems, watershed management employs multiple evaluation criteria, among them are the potential areas of intervention that can be addressed via environmental zoning (EZ) [9,10,16]. For zoning and management, it is necessary to start from the watershed concept using satellite monitoring and evaluation [1], as well as information on socioeconomic and biophysical characteristics [2,4].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…However, some authors highlight that coordination between planning at RBD and planning (SDAGE) at the municipal level (SAGE) may be an issue in terms of implementation of measures. For instance, Christophe and Tina [77] highlighted that the municipalities may be more interested in re-election than in water protection, and this may be an obstacle for the implementation of some types of measures. In Spain, while many studies have focused on how coordination and participation are achieved at regional level, the capacity of CH to coordinate the planning at RBD level is not evident form the analysed literature.…”
mentioning
confidence: 99%
“…Environmental zoning often reflects the interests of the social group controlling this political process (Boschet & Rambonilaza, 2015). One suggestion for addressing this is through the use of rescaling, such as a shift from provincial to watershed-based management systems.…”
Section: Theoretical Perspectivementioning
confidence: 99%